2000
DOI: 10.1074/jbc.275.14.10582
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DsbA-insensitive Folding of Escherichia coli Heat-stable Enterotoxin STa in Vitro

Abstract: To study the folding of human Escherichia coli heatstable enterotoxin STh, we used the major protein subunit of CS31A fimbriae (ClpG) as a marker of STh secretion and a provider of a signal peptide. We established that STh genetically fused to the N or C terminus of ClpG was able to mobilize ClpG to the culture supernatant while still retaining full enterotoxicity. These features indicate that the STh activity was not altered by the chimeric structure and suggest that spatial conformation of STh in the fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…1. Plasmids pEH838, pEHSTC22 [12,13] and pEHProSTC28 [12,13] derived from pEH524 [14], a vector carrying the clp gene cluster that codes for the ClpG export machinery required for the biogenesis of CS31A fimbriae [14] and the secretion of ClpG‐STh fusion proteins by E. coli DH5 α [13]; the wild‐type clpG gene from pEH524 was replaced either by the mutated clpG gene from pHPCO838 [12,13], giving pEH838, or by the clpG :: sth fusion genes from pSTC22 and pProSTC28, leading to pEHSTC22 and pEHProSTC28, respectively. Plasmid pSTCDM1 was made by inserting a double‐stranded oligonucleotide coding for the entire mature STh with glycine and leucine simultaneously substituted for Pro 13 and Ala 14 amino acid residues, between the Hpa I and Xba I sites of pHPCO838.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Plasmids pEH838, pEHSTC22 [12,13] and pEHProSTC28 [12,13] derived from pEH524 [14], a vector carrying the clp gene cluster that codes for the ClpG export machinery required for the biogenesis of CS31A fimbriae [14] and the secretion of ClpG‐STh fusion proteins by E. coli DH5 α [13]; the wild‐type clpG gene from pEH524 was replaced either by the mutated clpG gene from pHPCO838 [12,13], giving pEH838, or by the clpG :: sth fusion genes from pSTC22 and pProSTC28, leading to pEHSTC22 and pEHProSTC28, respectively. Plasmid pSTCDM1 was made by inserting a double‐stranded oligonucleotide coding for the entire mature STh with glycine and leucine simultaneously substituted for Pro 13 and Ala 14 amino acid residues, between the Hpa I and Xba I sites of pHPCO838.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pSTCDM1 was made by inserting a double‐stranded oligonucleotide coding for the entire mature STh with glycine and leucine simultaneously substituted for Pro 13 and Ala 14 amino acid residues, between the Hpa I and Xba I sites of pHPCO838. Because of many unsuccessful attempts to subclone the fusion genes from pSTC17 [12,13] and pSTCDM1 into pEH524, we trans‐complemented pSTC17 and pSTCDM1 with pDSPH524 [15], which is pEH524 with clpG deleted, for permitting secretion of fusion proteins. Gene fusions were checked by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Other results are in conflict with this view as deletion of the pro sequence or the STa peptide leads to detection of STa or pro peptide in the supernatant of cells, clearly indicating that the pro region can cross the outer membrane [38]. Other studies showed that various fusion proteins consisting of STa and the major subunit ClpG of E. coli CS31A fimbriae antigen are secreted across the outer membrane and that the disulfide bonds in the bioactive STa were formed extracellularly by a DsbA-independent mechanism possibly involving molecular oxygen [39,40]. However, these authors also showed that the export of their fusion proteins was dependent on the CS31A secretion pathway and might differ substantially from the secretion of native STa.…”
Section: Structure Of St Peptidesmentioning
confidence: 99%
“…1. Plasmids pEH838, pEHSTC22 [12,13] and pEHProSTC28 [12,13] derived from pEH524 [14], a vector carrying the clp gene cluster that codes for the ClpG export machinery required for the biogenesis of CS31A ¢mbriae [14] and the secretion of ClpG-STh fusion proteins by E. coli DH5 K [13]; the wild-type clpG gene from pEH524 was replaced either by the mutated clpG gene from pHPCO838 [12,13], giving pEH838, or by the clpG: :sth fusion genes from pSTC22 and pProSTC28, leading to pEHSTC22 and pEHProSTC28, respectively. Plasmid pSTCDM1 was made by inserting a double-stranded oligonucleotide coding for the entire mature STh with glycine and leucine simultaneously substituted for Pro 13 and Ala 14 amino acid residues, between the HpaI and XbaI sites of pHPCO838.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%
“…Plasmid pSTCDM1 was made by inserting a double-stranded oligonucleotide coding for the entire mature STh with glycine and leucine simultaneously substituted for Pro 13 and Ala 14 amino acid residues, between the HpaI and XbaI sites of pHPCO838. Because of many unsuccessful attempts to subclone the fusion genes from pSTC17 [12,13] and pSTCDM1 into pEH524, we trans-complemented pSTC17 and pSTCDM1 with pDSPH524 [15], which is pEH524 with clpG deleted, for permitting secretion of fusion proteins. Gene fusions were checked by sequencing.…”
Section: Construction Of Plasmidsmentioning
confidence: 99%